The Anthropological Approach To Conflict Management By Kodam Xvii Kasuari In West Papua - Lubis, Arief Fahmi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
After the incident of the attack on a military rayon command post in Kisor, Maybrat, West Papua Province occurred, people felt scared & threatened, and decided to flee to the forest. In addressing this situation, the Regent of Maybrat called on his people who were still displaced to return to their respective homes or villages. The addition of personnel of Kodam XVIII Kasuari in that location was not for a military operation but rather looking for the perpetrators of criminal acts of terrorism because they had caused tremendous fear in the local community, making them flee into the forest. This study aimed at examining the subject matter based on the scope and identification of the aforementioned problems through a normative juridical approach. Moreover, the researchers also included juridical-historical and juridical-political approaches based on the scope and identification of the problems. In this study, the researchers applied normative and empirical legal research methods at the same time. However, the researchers focused more on the normative legal research method, while the empirical legal research method was used to obtain supporting information. The object of this study was Kodam XVIII Kasuari which always tries to eliminate the bad culture of the Arfak mountain community, especially daily activities that clash with criminal acts (e.g., presenting firearms as a dowry). In addressing this problem, Kodam XVIII Kasuari had used various ways with the anthropological approach. This approach had been fully implemented by soldiers in West Papua within the framework of territorial operations in the aspect of education, raising awareness, and enforcing national laws in the communities in West Papua.